Komorbidnost depresije in spolne disfunkcije pri pacientih ambulante za zdravljenje spolnih motenj - Lučovnik, Miha (Medicinski razgledi, 2006)
Sexual dysfunction and depression often occur together, however the causal relation is unclear and has not been studied enough. Sexual dysfunction secondary to depression has been well studied, but less is known about prevalence of depressive symptoms among patients with sexual dysfunction. The aim of our study was to find out whether the depression was more common among young people with psychogenic sexual dysfunction waiting to be treated at the clinic for sexual disorders than among young people without problems with sexuality. We also tried to find out whether the sexual dysfunction was connected with sexual abused in childhood and whether the negative attitudes of original family toward sexuality had any impact on later sexual disfunction. 25 young people between 20 and 35 years of age with nonorganic sexual dysfunction, who were on waiting list to be treated in the outpatient department for sexual disorders treatment were included in the cross-sectionalstudy. Depressive symptoms and history of childhood sexual abuse were more common in the group of patients with sexual dysfunction. Majority of them also felt the negative impact of their parents attitudes towards sexuality.
Keywords: Depresija; Depression; Impotenca; Impotence; Soobolevnost; Comorbidity; Adult; ankete; Odrasli; Questionnaires; mladina; therapy; zdravljenje